Ethanol and carcinogenesis - Seitz, Helmut K. (Alcohol related diseases in gastroenterology ; with 38 tables, 1985)
Clinically, a link between alcoholism and certain types of cancer has been observed for many years. A great number of epidemiologic studies has shown an association between excessive drinking of alcoholic beverages and cancer of the oropharynx (Wynder et al. 1957; Keller 1967; Rothman and Keller 1972; Alcohol and Health 1975; Feldmann et al. 1975; Fortier 1975; Bross and Coombs 1976; Graham et al. 1977; McCoy 1978), the larynx (Vincent and Marchetta 1963; Gregoriades 1974; Alcohol and Health 1975; McMichael 1978; Tuyns 1978; Wynder et al. 1976; Tuyns 1979), and the esophagus (Wynder et al. 1957; Wynder and Bross 1961; Tuyns 1970; Schoenberg et al. 1971; Tuyns and Masse 1973; Wynder and Mabuchi 1973; Schottenfeldt et al. 1974). In a series of studies (Wynder et al. 1956a, b, 1957; Wynder and Bross 1957) heavy drinkers were found to have roughly a tenfold increased risk of developing cancer of the mouth. Subjects who drink heavily often also smoke heavily. This later fact was first taken into account by Flamant et al. (1964), who assessed both factors and reported that there was a “strong” association of alcohol intake with cancer of these sites that come most directly in contact with alcohol (tongue, hypopharynx, larynx, esophagus). It was calculated that 76% of these cancers in males could be eliminated if exposure to alcohol and tobacco were avoided (Rothman and Keller 1972). The risk of developing oral cancer for a heavy drinker who smokes was 6-15 times higher than for nondrinkers and nonsmokers (Fortier 1975; Feldman et al. 1975).
Gesehen am 05.12.2024